Concentration and CO2 Emissions in Seagrass Ecosystem Inner Ambon Bay - Krisye, Krisye; Fendjalang, Sophia N. M; Rahman, Rahman (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2023)
This study aims to analyze the concentration and emission of carbon dioxide gas in seagrass species found in Tanjung Tiram and Halong Beach. The gas extraction method uses a hood, and the analysis of its concentration or emissions refers to the gas chromatograph method (GC-MS). The results showed that the concentration of CO2 gas in each species between locations was relatively different. In Tanjung Tiram seagrass, the largest concentration was found in E. acoroides species at 616.82 ppm and the lowest in H. pinifolia species at 594.89 ppm. Meanwhile, the largest concentration of CO2 gas in Halong was found in T. hemprichii and C. rotundata species with values of 651.19 ppm and 609.68 ppm, respectively, and the lowest was also found in H. pinifolia species at 471.18 ppm. The range of CO2 emissions in Tanjung Tiram is 7.00 – 16.98 mg/m2/hour, with the highest emissions found in H. pinifolia (16.98 mg/m2/hour) and the lowest in E. acoroides (7.00 mg/m2/hour). Halong's largest emissions in seagrass are found in C. rotundata and H. pinifolia, respectively, at 26.37 mg/m2/hour and 25.84 mg/m2/hour. In comparison, the lowest is found in T. hemprichii, which is 7.66 mg/m2/hour.